2020
DOI: 10.3390/cancers12061351
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatocellular Carcinoma after HCV Clearance by Direct-Acting Antivirals Treatment Predictive Factors and Role of Epigenetics

Abstract: Direct-acting antivirals (DAAs) induce a rapid virologic response (SVR) in up to 99% of chronic hepatitis C patients. The role of SVR by DAAs on the incidence or recurrence of hepatocellular carcinoma (HCC) is still a matter of debate, although it is known that SVR does not eliminate the risk of HCC. In this review, we made an updated analysis of the literature data on the impact of SVR by DAAs on the risk of HCC as well as an assessment of risk factors and the role of epigenetics. Data showed that SVR has no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 102 publications
(153 reference statements)
2
58
0
4
Order By: Relevance
“…Studies on this SNP were performed only on coronary artery disease by Zain et al 15 and Cresci et al 24 The present study also reported a significant difference in the genotypes of rs1503298 in the male cohort. These results are matched with Rinaldi et al, 25 who showed that male sex is one of the significant predictors of the onset of HCC.…”
Section: Discussionsupporting
confidence: 89%
“…Studies on this SNP were performed only on coronary artery disease by Zain et al 15 and Cresci et al 24 The present study also reported a significant difference in the genotypes of rs1503298 in the male cohort. These results are matched with Rinaldi et al, 25 who showed that male sex is one of the significant predictors of the onset of HCC.…”
Section: Discussionsupporting
confidence: 89%
“…We chose to use the PSM FUZZY extension command in Python to balance the SOF-based and SOF-free groups. Variables used in the PSM model included sex, age, serum albumin, ALT, platelet count, AFP, eGFR, cirrhosis, and treatment experience, all of which are clinically important variables for predicting the development of HCC according to recent reports [4][5][6][7][8][11][12][13]16,17]. Caliper matching of the propensity scores was done, and pairs were matched to within a range of 0.2 standard deviations of the logit of the propensity scores [35].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, with the advent of direct-acting antivirals (DAAs) in 2013, the rates of sustained viral response (SVR) now range from 85% to almost 100%, depending on the HCV genotype and the presence of cirrhosis or active HCC [1][2][3]. This has contributed to a reduction of the risk for HCC [4][5][6][7][8] and the number of patients requiring a liver transplant [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar context, another study reported that sofosbuvir (SOF) may activate epidermal growth factor receptor (EGFR)-dependent pathways, inducing liver-related pathological processes [ 14 ]. Nevertheless, subsequent studies have failed to reproduce such kinds of data systematically yet, indicating that there has been no difference in the risk of HCC occurrence or recurrence following SVR from DAA- vs. IFN-based therapy so far [ 15 , 16 , 17 , 18 ]. However, Ogawa et al [ 19 ] recently proposed a trend toward a higher short-term HCC incidence in a subgroup treated with a specific DAA, i.e., SOF.…”
Section: Introductionmentioning
confidence: 99%